Metode Kerja Berorientasi Ergonomi pada Proses Pengelapan Kaleng Sarden Menurunkan Keluhan Muskuloskeletal dan Kelelahan Pekerja di PT. BMP Negara, Bali - Negara, Ni Luh Gede Aris Maytadewi; Sutjana, I Dewa Putu; Adiputra, Luh Made Indah Sri Handari (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2019)
Industrial activities developed from households to large-scale industries, including the development of industries in the field of canning fish. Worker health is one of the important things in a company, can be achieved by choosing the right work method. This study was conducted to determine whether ergonomic oriented working methods in the process of wiping canned sardines can reduce musculoskeletal complaints and fatigue in workers. The study design was two period cross over pre and post-test group desig). The research was conducted at PT. BMP Negara. It was held in December 2016. Total sample were 18 workers who wiping cans of sardines. The difference in conditions between before and after activities using ergonomic un-oriented working methods and ergonomic oriented working methods are compared and tested statistically. Comparison tests were carried out on scores of musculoskeletal complaints and worker fatigue. The results showed that ergonomic oriented working methods decreased of musculoskeletal complaints 17.82% (p<0.05) and fatigue score of 11.86% (p<0.05). The conclusion of this study is that ergonomic oriented working methods in the process of wiping sardine cans reduce musculoskeletal complaints and work fatigue of workers in PT. BMP Negara.